Secretory cell outgrowths, p53 signatures, and serous tubal intraepithelial carcinoma in the fallopian tubes of patients with sporadic pelvic serous carcinoma - Neha Mittal; Radhika Srinivasan; Nalini Gupta; Arvind Rajwanshi; Raje Nijhawan; Upasana Gautam; Swati Sood; Lakhbir Dhaliwal (Wolters Kluwer Medknow Publications, 2016)
Context: High-grade serous carcinomas of ovarian, tubal, and peritoneal origin are together referred as pelvic serous carcinoma. The fallopian tubes, ovarian surface epithelium, and the tuboperitoneal junctional epithelium are all implicated in pelvic serous carcinogenesis. Aims: The aim of this study is to identify putative precursor lesions of serous carcinoma including secretory cell outgrowths (SCOUTs), serous tubal intraepithelial carcinoma (STIC), and p53 signatures and assign its probable site of origin. Settings and Design: Prospective case-control study of consecutive specimen comprising 32 serous carcinomas and 31 controls (10 normal adnexa, 10 benign and 6 atypically proliferative surface epithelial tumors, and 5 other carcinomas). Subjects and Methods: Sectioning and extensive examination of the fimbrial end (SEE-FIM) protocol along with immunohistochemistry for Bcl-2, p53, and Ki-67 was employed for evaluating invasive carcinoma and precursor lesions in cases versus controls. Results: SCOUT, p53 signatures, and STIC were most frequent in the serous carcinomas. p53 signatures and STIC were always seen in the fimbrial end. STICs were exclusively present in serous carcinomas, more common in ipsilateral tubes of cases with dominant ovarian mass. Multifocal p53 signatures with STIC were seen in 7 (21.9%) cases. STIC was present with or without an invasive carcinoma in 25% and in 6.25% of cases of pelvic serous carcinomas, respectively. The junctional epithelia did not show any lesion in any group. Conclusions: SEE-FIM protocol is recommended for evaluation of sporadicpelvic (ovarian/tubal/peritoneal) serous carcinoma. Based on the presence of STIC or invasive carcinoma, nearly 60% of all pelvic serous carcinomas are of fallopian tubal origin.